1988
DOI: 10.1007/bf00316641
|View full text |Cite
|
Sign up to set email alerts
|

Dermal toxicity of Fusarium toxins in combinations

Abstract: T 2 toxin (T 2), diacetoxyscirpenol (DAS), fusarenon X (FX) and butenolide (Bd) at concentrations of 0.2, 0.3, 5 and 10 micrograms/site, respectively, were applied individually and in combinations on shaved skin of guinea pigs. Erythema and induration were observed on skin patches treated with the toxins. Increase in the thickness of stratum malpighii was the major histological change observed. Mild to moderate degeneration of fibrocytes and cellular infiltration were found in the corium of skin treated with F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

1992
1992
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 12 publications
0
11
0
1
Order By: Relevance
“…Erythema and induration were observed on skin patches treated with the toxins. These findings correlated histologically with the thickening of stratum malpighii, mild to moderate degeneration of fibrocytes, and cellular infiltration (22).…”
Section: Pathogenesis Of Infectionmentioning
confidence: 60%
“…Erythema and induration were observed on skin patches treated with the toxins. These findings correlated histologically with the thickening of stratum malpighii, mild to moderate degeneration of fibrocytes, and cellular infiltration (22).…”
Section: Pathogenesis Of Infectionmentioning
confidence: 60%
“…Ingestion of DON, commonly referred to as vomitoxin, or 15 acetyl-DON could produce the symptoms described above as characteristic of trichothecene mycotoxins. (26,(28)(29)(30) The health effects from respiratory exposures to mycotoxins is an area that is less widely studied than the health effects from mycotoxin ingestion. Since mycotoxins are largely nonvolatile, most respiratory exposure to mycotoxins would occur by inhalation of aerosolized spores, hyphae, and small particles of fungal substrate.…”
Section: Mycotoxinsmentioning
confidence: 99%
“…(Cole and Cox 1981;Thrane 2001). There is increasing evidence that butenolide can induce diverse toxicities, such as cytotoxicity in several cell lines (Vesonder et al 1993), dermal toxicity in guinea pigs characterized by erythema and induration on skin (Bhavanishankar et al 1988), and subacute inhalation toxicity in hamsters, as shown by eye irritation, salivation, increased liver weight, and growth retardation (Feron et al 1979). Keshan disease is a well-known endemic cardiomyopathy which is prevalent in certain areas of China.…”
Section: Introductionmentioning
confidence: 99%